2015
DOI: 10.1177/0192512115577231
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: Euroscepticism, from the margins to the mainstream

Abstract: With the advent of the Eurozone crisis, Euroscepticism has become increasingly mainstreamed. This is discernible across Europe at the level of public opinion, among political parties and civil society groups, within the EU institutions themselves and in terms of changing and more challenging media discourses. Against the backdrop of the 2014 European elections and a potential referendum on UK membership of the EU, the purpose of this article is to introduce an evolving debate. It begins with discussion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 33 publications
(21 reference statements)
1
61
0
5
Order By: Relevance
“…Here some strands in critical border studies help to analyse the potential consequences of such views, warning how any divergence on the part of the Schengen security community from the path of regional integration and solidarity could send Europe back to the traditional power politics of national interests, self-reliance and mistrust (Alkopher and Blanc 2016). Such a return is possible since right-wing Eurosceptic populism has become mainstreamed (Brack and Startin 2015), especially in our cases of the UK (Auel and Raunio 2014) and Finland (Leruth 2015). In this situation, voices such as our third view portray the "people" being justifiably concerned about increasing immigration and surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here some strands in critical border studies help to analyse the potential consequences of such views, warning how any divergence on the part of the Schengen security community from the path of regional integration and solidarity could send Europe back to the traditional power politics of national interests, self-reliance and mistrust (Alkopher and Blanc 2016). Such a return is possible since right-wing Eurosceptic populism has become mainstreamed (Brack and Startin 2015), especially in our cases of the UK (Auel and Raunio 2014) and Finland (Leruth 2015). In this situation, voices such as our third view portray the "people" being justifiably concerned about increasing immigration and surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Spain has experienced some left-wing Euroscepticism amidst its economic hardships, while support for the Romanian Eurosceptic Greater Romania Party is marginal (Halikiopoulou andVasilopoulou 2014, Brack andStartin 2015). 2.…”
Section: Notesmentioning
confidence: 99%
“…2 Geert Wilders has been a representative in the Dutch Lower Chamber since 1998 and Marine Le Pen grew up involved in the politics of her father's party (of which she has been an active member since 1986). 3 For an insight into this phenomenon, which can been categorized under the umbrella term of Euroscepticism, see Brack and Startin (2015). 4 To illustrate, the prime-minister of the Netherlands, Mark Rutte, gave an interview in which he stated that normality should be the new norm.…”
Section: Notesmentioning
confidence: 99%
“…Research shows that Euroskepticism is stronger among opposition parties (De Vries -Edwards 2009;Taggart 1998). However, with the economic crisis of 2008, Euroskepticism has become increasingly mainstream (Meijers 2015;Brack -Startin 2015). Not only have radical and extreme parties increased their Euroskepticism, so have several mainstream parties, especially those that are in opposition (Conti et al 2017).…”
Section: H4 Political Extremism Negatively Affects Euroenthusiasmmentioning
confidence: 99%
“…Recent studies of Euroskepticism have found that the economic crisis of 2008, its length, the complexities of the bargaining process, and the unpopular nature of the solutions that were applied decreased support for the EU and boosted disappointment and disbelief in its mediating capacity among various constituencies (De Wilde -Zurn 2012). For instance, Brack and Startin (2015) consider that, because of the economic crisis of 2008, Euroskepticism has entered the mainstream and is now present across Europe at the level of public opinion -among political parties and civil society groups, within the EU institutions themselves, and in the media. However, other research demonstrates that even though the economic crisis of 2008 in the EU catalyzed the politicization of crisis management policies, spurred debates about the integration of the Eurozone and polarized opinions about the future of the EU it did not necessarily produce an indisputably downward trend in the support for the EU (Serricchio et al 2013;Armingeon -Ceka 2014;Teney 2016).…”
Section: Introductionmentioning
confidence: 99%